Thinking on your feet 2 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Striking a Balance. A guide to enhancing the effectiveness of non-governmental organisations in international development A Fowler, Earthscan, London, 1997. 313 pp. ISBN 1 85383 325 8 CTA number 970. 40 credit points.